New Developments and Old Dilemmas in Ontario’s Resuscitation Policy at the End of Life - Apramian, Tavis; Szego, Michael; Langlois, Dave (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
This paper deals with changes in code status policy in Ontario and endorses a new College of Physicians and Surgeons of Ontario (CPSO) policy. We argue that the recent policy changes in this area necessitate an active educational strategy around end-of-life care to prevent harm to dying patients.